2013
DOI: 10.1016/j.susc.2012.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemistry of glycine on Pt{111} in different aqueous environments

Abstract: Adsorption of glycine on Pt{111} under UHV conditions and in different aqueous environments was studied by XPS (UHV and ambient pressure) and NEXAFS. Under UHV conditions, glycine adsorbs in its neutral molecular state up to about 0.15 ML. Further deposition leads to the formation of an additional zwitterionic species, which is in direct contact with the substrate surface, followed by the growth of multilayers, which also consist of zwitterions. The neutral surface species is most stable and decomposes at 360 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 65 publications
2
41
0
Order By: Relevance
“…Surprisingly then, our results show that, over a wide range of temperature and pressure, the pure water and glycine overlayers are more stable than the mixed phases, suggesting that the ability to form intermixed hydrogen-bonded networks between the anionic amino acid and water is not the reason behind the extraordinary reactivity between H 2 O and gly (or ala). If we consider that Shavorskiy et al 67 found no evidence of reaction between glycine and water when the Cu{110} surface was presaturated by glycine, we can also exclude the fact that the reaction could proceed through an Eley-Rideal mechanism; therefore the only alternative remaining is that, at submonolayer coverage, the glycine islands are surrounded by a reactive water boundary region. 3 The phase diagram for the glycine/H 2 O equilibrium (without vdW corrections) as a function of the surface temperature (T) and water pressure P(H 2 O).…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly then, our results show that, over a wide range of temperature and pressure, the pure water and glycine overlayers are more stable than the mixed phases, suggesting that the ability to form intermixed hydrogen-bonded networks between the anionic amino acid and water is not the reason behind the extraordinary reactivity between H 2 O and gly (or ala). If we consider that Shavorskiy et al 67 found no evidence of reaction between glycine and water when the Cu{110} surface was presaturated by glycine, we can also exclude the fact that the reaction could proceed through an Eley-Rideal mechanism; therefore the only alternative remaining is that, at submonolayer coverage, the glycine islands are surrounded by a reactive water boundary region. 3 The phase diagram for the glycine/H 2 O equilibrium (without vdW corrections) as a function of the surface temperature (T) and water pressure P(H 2 O).…”
Section: Resultsmentioning
confidence: 99%
“…25,26 Our recent work on the adsorption of chiral modifiers on Ni, Pt and Cu surfaces has shown that the combination of XPS and NEXAFS is very powerful in characterizing the adsorption complex in terms of chemical state, bond coordination and molecular orientation. 19,[27][28][29][30] These spectroscopies do not depend on long-range order and can even be applied under near-ambient pressure conditions. They are therefore well suited for the study of chiral modifiers and reactants on Ni surfaces.…”
Section: 24mentioning
confidence: 99%
“…[46] In line with these calculations, recent experiments show that glycine adsorbs in its pristine form on Pt(111) at low coverages, showing that, similar to Pd(111) surfaces the molecule-molecule interaction stabilizes the zwitterionic form. [46,51] In the present paper, we concern ourselves with low-coverage adsorption where molecule-molecule interaction is negligible.…”
Section: Introductionmentioning
confidence: 99%